Public Policy for Start-up Entrepreneurship with Venture Capital and Bank Finance - Christian Keuschnigg; Søren Bo Nielsen (Center for Economic Studies and ifo Institute (CESifo), 2003)
This paper proposes and analyses a model of start-up investment. Innovative entrepreneurs are commercially inexperienced and can benefit from venture capital support. Only part of them succeed in matching with a venture capitalist while the rest must resort to standard bank finance. We consider a number of policies to promote entrepreneurship and venture capital backed innovation.
Keywords: 330; venture capital bank finance; matching; moral hazard; public policy